2002
DOI: 10.4269/ajtmh.2002.67.67
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of West Nile virus in a New York City captive wildlife population.

Abstract: Abstract. An outbreak of West Nile virus (WNV) in and around New York City during the late summer of 1999 was the cause of extensive mortality among free-ranging birds. Within the Bronx Zoo/Wildlife Conservation Park, viral activity was also observed and produced some morbidity and mortality among specimens in the zoo's bird collection and probably caused morbidity in at least one specimen from the zoo's mammal collection. To determine the extent of the outbreak and attempt to ascertain the temporal appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 22 publications
1
86
2
Order By: Relevance
“…Two studies have shown that sensitivity to WNV increases with age: one on geese with an Israeli strain (McLean et al, 2002) and another on chickens with an Egyptian strain (Malkinson et al, 2001). Although both the Egyptian and Israeli strains closely resemble the NY99 strain present in North American, neither geese nor chickens are passerines (Ludwig et al, 2002;Meulen et al, 2005), which limits the comparability of these results to our findings. In 2002, during a WNV epidemic in an Ontario owl population, HY owls were more resistant to WNV than were adult owls (Gangz et al, 2004).…”
Section: Characteristics Of Wnv-positive American Crow Mortalitycontrasting
confidence: 38%
See 2 more Smart Citations
“…Two studies have shown that sensitivity to WNV increases with age: one on geese with an Israeli strain (McLean et al, 2002) and another on chickens with an Egyptian strain (Malkinson et al, 2001). Although both the Egyptian and Israeli strains closely resemble the NY99 strain present in North American, neither geese nor chickens are passerines (Ludwig et al, 2002;Meulen et al, 2005), which limits the comparability of these results to our findings. In 2002, during a WNV epidemic in an Ontario owl population, HY owls were more resistant to WNV than were adult owls (Gangz et al, 2004).…”
Section: Characteristics Of Wnv-positive American Crow Mortalitycontrasting
confidence: 38%
“…This lower BCI could have been caused by dehydration or poor body condition after WNV infection. The high sensitivity of American Crows to WNV, the high rate of mortality following WNV infection, and the swiftness of death-approximately seven days post-infection (Ludwig et al, 2002;Komar et al, 2003)-could cause major dehydration or a lowered BCI in the infected American Crow.…”
Section: Characteristics Of Wnv-positive American Crow Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Serosurveys among equines living in WNV-endemic areas, as well as results of WNV experimental infections of horses, indicate that most equine infections are inapparent or result in only mild clinical illness (4-7). Most reported WNV-associated bird deaths in the United States have been in crows and blue jays (2,8), two species with a relatively high case-fatality rate; however, many other bird species are naturally infected with the virus and have few or no deaths (8)(9)(10)(11). Because the current WNV surveillance systems in the United States are largely disease-and death-based (cases of human meningoencephalitis, equine encephalitis, dead birds), the actual prevalence of WNV infection among humans and other susceptible vertebrate hosts and the intensity of virus transmission are underestimated.…”
Section: Researchmentioning
confidence: 99%
“…Mosquitoes are the primary vectors for WNV, and wild birds are the principal hosts (Hubalek and Halouzka, 1999;Campbell et al, 2002;McLean et al, 2002). Evidence of WNV infections in a variety of vertebrates (Steele et al, 2000;Komar et al, 2001;Ludwig et al, 2002;Lichtensteiger et al, 2003;Steinman et al, 2003;Heinz-Taheny et al, 2004) suggests that WNV is widespread in wildlife, and other vertebrate hosts might serve as an overwintering and maintenance reservoir for WNV.…”
mentioning
confidence: 99%